2017
DOI: 10.3390/f8090348
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs Responsive to Witches’ Broom Disease in Paulownia tomentosa

Abstract: Paulownia witches' broom (PaWB) disease caused by phytoplasmas is a fatal disease that leads to considerable economic losses. Long non-coding RNAs (lncRNAs) have been demonstrated to play critical regulatory roles in posttranscriptional and transcriptional regulation. However, lncRNAs and their functional roles remain poorly characterized in Paulownia. To identify lncRNAs and investigate their roles in the response to PaWB phytoplasmas, RNA sequencing was performed for healthy Paulownia tomentosa, PaWB-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…In plant-pathogen interactions, using an RNA sequencing approach, 125 putative stress-responsive lncRNAs that are induced by powdery mildew infection have been identified in wheat 24 . A number of lncRNAs have been identified in Paulownia witches’ broom-infected Paulownia tomentosa by high-throughput sequencing 25 . In addition, Arabidopsis thaliana lncRNAs have been found to act in Arabidopsis resistance to Fusarium oxysporum 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In plant-pathogen interactions, using an RNA sequencing approach, 125 putative stress-responsive lncRNAs that are induced by powdery mildew infection have been identified in wheat 24 . A number of lncRNAs have been identified in Paulownia witches’ broom-infected Paulownia tomentosa by high-throughput sequencing 25 . In addition, Arabidopsis thaliana lncRNAs have been found to act in Arabidopsis resistance to Fusarium oxysporum 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, lncRNAs have been investigated in many plants under biotic stresses [19]. In this study, we identified 229 DELs that may be PaWB-related lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Plant lncRNAs play important roles in seed development (Kiegle et al ., ), photomorphogenesis (Wang et al ., ), fruit development (Zhu et al ., ; Wang et al ., , ; Li et al ., ), microRNA (miRNA) silencing (Wang et al ., ), miRNA precursors (Chen et al ., ; Joshi et al ., ) and biotic and abiotic stress responses (Qin et al ., ; Wang et al ., ). In studies examining plant−pathogen interactions, a set of Paulownia tomentosa lncRNAs has been identified in Paulownia witches’ boom‐infected P. tomentosa by high‐throughput sequencing (Wang et al ., ). In wheat, powdery mildew‐induced lncRNAs were identified and characterized (Xin et al ., ), and four wheat lncRNAs play important roles in wheat− Puccinia striiformis interaction (Zhang et al ., ).…”
Section: Introductionmentioning
confidence: 97%